Metabolic Profile of Patients with Recurrent Nephrolithiasis: A Hospital Based Cross-Sectional Study from a Tertiary Care Centre in Nepal (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Nephrolithiasis is a recurrent condition with multifactorial metabolic causes that vary across populations. Identifying metabolic abnormalities among recurrent multiple stone formers is essential for targeted prevention. This study aimed to evaluate the spectrum and frequency of metabolic derangements among patients with recurrent nephrolithiasis including both recurrent single- and multiple-stone formers presenting to a tertiary care center in Nepal.Material and Methods: This hospital based cross-sectional observational study was conducted in the Department of Nephrology, Bir Hospital, from February 2018 to January 2019. Adult patients (≥18 years) with a history of recurrent or multiple renal stones confirmed by ultrasonography were included. Demographic and clinical data were recorded, and 24-hour urine samples were analyzed for calcium, citrate, oxalate, uric acid, and volume. Serum calcium, phosphate, uric acid, and creatinine were measured. Metabolic abnormalities were defined using standard thresholds, and data were analyzed using descriptive statistics, the Chi-square test, and logistic regression with R version 4.4.1. A p-value